Terminologi Wasaṭiyah dalam al-Qur’an - Muttaqin Muttaqin (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2017)
This paper discusses the concept of wasaṭiyah as one of seminal concept in several verses of al-Qur’an. The research focuses on five verses of al-Qur’an representing words of wasaṭiyah. The words are: wasaṭan (fair and chosen people) in al-Baqarah [2]: 143, fawasaṭna (middle) in al-‘Ādiyāt [100]: 5, awsaṭ (from average food) in al-Maidah [5]: 89, awsaṭuhum (the most moderate of them) in al-Qalam [68]: 28, and al-wusṭa (salah of wusṭa) in al-Baqarah [2]: 238. According to its etymology, there is no strong correlation among these words. However, if it approached further by study tafseer, the correlation of one another will be found. Wasaṭiyah is the seminal concept, which should be existed in every Muslim life. It has its own characteristics, which demonstrate the existence of people who admitted themselves as Muslim. Such as to be justice, to avoid the despot, to be truthful, and the all of these features prove is them as good people. In other hand, these words have similarity in accordance with the terms of definition and terminology. It can be traced from the views of Muslim Scholars such as Abdullah Abdul Muhsin al-Turkiy, Abdullah bin Sulaiman al-Ghafili, and Ali Muhammad al-Salabiy.